Effect of quorum sensing signals produced by seaweed-associated bacteria on carpospore liberation from Gracilaria dura - Singh, Ravindra Pal; Baghel, Ravi S.; Reddy, C. R. K.; Jha, Bhavanath (Frontiers in Plant Science, 2015)
Epiphytic and endophytic bacteria associated with green macroalgae Ulva (U. fasciata and U. lactuca) and red macroalgae Gracilaria (G. corticata and G. dura) have been identified from three different seasons to evaluate the effect of quorum sensing molecules on carpospores liberation from Gracilaria dura. The bacterial isolates belonging to the orders Bacillales, Pseudomonadales, Alteromonadales and Vibrionales were present in all seasons, whereas Actinomycetales and Enterobacteriales were confined to pre-monsoon and post-monsoon seasons, respectively. Among all the Gram-negative bacteria, seven isolates were found to produce different types of N-acyl homoserine lactones (AHLs). Interestingly, Shewanella algae produced five types of AHL: C4-HSL, HC4-HSL, C6-HSL, 3-oxo-C6-HSL and 3-oxo-C12-HSL. Subsequently, the AHLs producing bacterial isolates were screened for carpospore liberation from G. dura and these isolates were found to positively induce carpospore liberation over the control. Also, observed that carpospore liberation increased significantly in C4- and C6-HSL treated cystocarps. Sodium dodecyl sulfate and native polyacrylamide gel electrophoresis of the total protein of the C4- and C6-HSL-treated cystocarps showed two specific peptide bands of different molecular weights (50 kDa and 60 kDa) as compared to the control, confirming their indirect effect on carpospore liberation.